CORRELATION BETWEEN PHYSICAL FITNESS AND MOTIVATION FOR PHYSICAL ACTIVITY IN CHILDREN WITH AUTISM SPECTRUM DISORDERS - Hamade, Ali; Petrusenko, Oleksandra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Information on the correlation of physical fitness indicators to indicators of motivation for physical activity (PA) in schoolchildren with autism spectrum disorders (ASD) is very limited. The lack of such information makes it impossible to collect informative tests that best assess the level of РА literacy. It also hampers the effective identification of appropriate and effective means for the formation of РА literacy among schoolchildren with ASD. The study aims at comparing the levels of physical fitness and motivation for PA in children with ASD with their peers without disorders; determining the degree of correlation between physical fitness and motivation for physical activity in children with ASD. Data were collected from two Ukrainian samples: 18 children with ASD aged 11–13 years, and 30 children aged 11–12 years without ASD diagnosis. Results. Most of the correlation coefficients between the indices of physical fitness and motivation for РА in children with ASD (9/12) are reliable. This suggests that motivation to РА (defined by the CAPL-2 methodology) is an informative criterion of РА literacy of children with ASD. Significant correlations with motivation for РА in schoolchildren with ASD were observed in the results of two exercise tests.